Depletion of Intracellular Glutamine Pools Triggers Toxoplasma gondii Stage Conversion in Human Glutamatergic Neurons - Bando, Hironori; Fukuda, Yasuhiro; Watanabe, Nina; Olawale, Jeje Temitope; Kato, Kentaro (Frontiers in Cellular and Infection Microbiology, 2022)
Toxoplasma gondii chronically infects the brain as latent cysts containing bradyzoites and causes various effects in the host. Recently, the molecular mechanisms of cyst formation in the mouse brain have been elucidated, but those in the human brain remain largely unknown. Here, we show that abnormal glutamine metabolism caused by both interferon-γ (IFN-γ) stimulation and T. gondii infection induce cyst formation in human neuroblastoma cells regardless of the anti-T. gondii host factor nitric oxide (NO) level or Indoleamine 2,3-dioxygenase-1 (IDO1) expression. IFN-γ stimulation promoted intracellular glutamine degradation in human neuronal cells. Additionally, T. gondii infection inhibited the mRNA expression of the host glutamine transporters SLC38A1 and SLC38A2. These dual effects led to glutamine starvation and triggered T. gondii stage conversion in human neuronal cells. Furthermore, these mechanisms are conserved in human iPSC-derived glutamatergic neurons. Taken together, our data suggest that glutamine starvation in host cells is an important trigger of T. gondii stage conversion in human neurons.